MAHAR DAN BHOKA (DILEKTIKA AGAMA DAN ADAT PADA MASYARAKAT MUNA DI KENDARI DALAM PERSPEKTIF HUKUM ISLAM) - Muhammad Alifuddin; Suhiat Suhiat; Laode Anhusadar (Universitas Islam Negeri Mataram, 2020)
This research is an ethnographic study of religious and traditional dialectics in marriage rituals in the Muna environment. All data in the study came from observations, in-depth interviews, and document studies. Considering that this research is related to aspects of law practice that live in the socio-cultural space, the data analysis is carried out using a hermeneutic phenomenological approach. The integration of bhoka as a value or amount of dowry in the perspective of Islamic law can be seen as urf. A serious problem related to the implementation of bhoka giving as a dowry value is more caused because in many cases the dowry which is actually the right of a wife is shifted into or divided among the family, even to some figures. adat who witnessed the process. This reality has the potential to violate the norms of applying dowries in Islamic law, thus necessitating new agreements to reformulate the pattern of implementing dowries and bhoka which can lead people to practice religion and customs side by side without any potential violations of values. Therefore if the bhoka itself can be categorized as sahih urf. However, the shift in the subject of the right to dowry which is assessed by bhoka, leads to the potential for violating the law, and or the creation of urf which is counterproductive to Islamic values.